Development of digital teaching materials in English subject at senior high school - Supriandi Supriandi; Muhammad Rais; Awaluddin Muin; Nurhikmah H; Bahri Bahri (Himpunan Pengembang Kurikulum Indonesia, 2025)
The use of digital teaching materials continues to evolve with advancements in information technology. This study aims to identify students’ needs, design digital teaching materials using Google Sites, assess their validity, measure practicality, and test effectiveness. The Research and Development (RnD) method was used, integrating three development models: ADDIE, 4D, and Dick and Carey. The resulting stages included define, design, development, implementation, evaluation, and dissemination. The research was conducted at SMA Negeri 1 Sinjai, involving 30 students, one subject teacher, and two expert validators (media and content). Data were collected through questionnaires and learning tests. The digital teaching material developed is an online learning website based on Google Sites, designed to be interactive, responsive, and user-friendly. The results showed that the digital teaching materials were rated as highly valid and very practical, based on student and teacher feedback, and effective, as indicated by student activity observations and post-test results. This digital teaching material is designed to serve as an innovative alternative, supporting a more interactive and meaningful learning process. Abstrak Pemanfaatan bahan ajar digital dalam proses pembelajaran terus berkembang seiring kemajuan teknologi informasi. Penelitian ini bertujuan untuk mengidentifikasi kebutuhan siswa terhadap bahan ajar digital, merancang bahan ajar digital berbasis google sites, menilai tingkat validitas, mengukur kepraktisan, dan menguji keefektifan bahan ajar tersebut. Pendekatan yang digunakan adalah metode Research and Development (RnD), dengan menggabungkan tiga model pengembangan yaitu ADDIE, 4D, dan Dick and Carey. Tahapan yang dihasilkan meliputi define, design, development, implementation, evaluation, dan disseminate. Penelitian dilaksanakan di SMA Negeri 1 Sinjai dengan melibatkan 30 siswa, 1 guru mata pelajaran, serta 2 validator (ahli media dan materi). Pengumpulan data menggunakan angket dan tes belajar. Bahan ajar digital yang dikembangkan dalam penelitian ini berupa sebuah situs pembelajaran berbasis google sites yang dapat diakses secara daring oleh siswa maupun guru. Situs ini dirancang dengan pendekatan yang interaktif, responsif, dan mudah digunakan. Hasil penelitian menunjukkan bahan ajar digital pada kategori sangat valid serta kategori sangat praktis berdasarkan respons siswa dan respons guru, dan kategori efektif pada observasi aktivitas siswa dan ketuntasan posttest. Pengembangan bahan ajar digital ini diharapkan dapat menjadi alternatif inovatif dalam mendukung proses pembelajaran yang interaktif dan bermakna. Kata Kunci: bahan ajar digital; bahasa Inggris; Google Sites; hasil belajar